MANAJEMEN LABA SEBAGAI RESPON PERUBAHAN TARIF PAJAK PENGHASILAN BADAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Anik Wahyu Ristiyanti; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2012)
This study aims to examine the company's response of change of Law Number 36 of 2008 concerning Income Tax Return For Corporate as a reduction of income tax rates in the years at 2009 and 2010 which in 2009 at 28% and 2010 decreased to 25%. This study also aims to determine the effect of tax incentives and non-tax incentives and a percentage of shares traded on the Stock Exchange for earnings management behavior. The sample that used for this study are manufacturing firms that listed on  Indonesia Stock Exchange, which has published their financial report from 2007 until 2010. Analysis method that used is multiple regression analysis to determine the effect of independent variables (taxplan, earnings pressure, debt levels, earnings bath, firm size, managerial ownership, percentage of outstanding shares in the Indonesian Stock Exchange) to the dependent variable (discretionary accruals) and different test T-test using one sample t-test. Difference test T-test was used to test for differences in the level of discretionary accruals between 2007, 2008, 2009 and 2010. The research results showed that before and after tax rate reduction, management has proven to earnings management through discretionary accruals. From the regression result that tax incentives and the percentage of shares traded on the Stock Exchange have a significant effect on discretionary accruals, while the non-tax incentives only earnings pressure (for losses companies), debts, and the percentage of outstanding shares on the Indonesian Stock Exchange (for profit companies) that significantly to discretionary accruals while the earning bath, firm size and managerial ownership does not significantly influence discretionary accrual.